Enhancing Choices Regarding the Administration of Insulin Among Patients With Diabetes Requiring Insulin Across Countries and Implications for Future Care - Mardare, Ileana; Campbell, Stephen M.; Meyer, Johanna C.; Sefah, Israel Abebrese; Massele, Amos; Godman, Brian (Frontiers in Pharmacology, 2022)
There are a number of ongoing developments to improve the administration of insulin in patients with diabetes, addressing the growing burden of diabetes across countries with its increasing morbidity, complications, mortality and costs and reduced health-related quality-of-lie (HRQOL). Recent developments to improve patient management thereby reducing hypoglycaemia and improving adherence to insulin regimens (including long-acting insulin analogues) and long-term outcomes, include the introduction of continuous glucose monitoring (CGM) systems and continuous subcutaneous insulin infusion systems, combined with sensor-augmented pump therapy and potentially hybrid closed-loops. The benefits of such systems have been endorsed by Endocrine Societies and governments. The National Institute for Health and Care Excellence endorsed the use of insulin pumps for patients with Type 1 Diabetes whose HbA1c levels are not currently being optimised. However, there are concerns with the low use of such systems across countries, exacerbated by their higher costs, despite studies suggesting their cost-effectiveness ratios are within accepted limits. This is inconsistent compared with positive reimbursement and funding decisions for new high-priced medicines for cancer and orphan diseases, with often limited benefits, given the burden of multiple daily insulin injections coupled with the need for constant monitoring. This is especially problematic in low- and low-middle income countries struggling to fund standard insulins on a daily basis, with the pandemic generating a parallel increase in the number of patients with non-communicable diseases with additional pressure on costs. Greater patient involvement, transparency in decision making, and evidence-based investment decisions should help to address such concerns in the future.